Modern approaches to assessment of PAHs bioavailability in soil for environmental toxicology research - Krektun, B. V.; Snitynskiy, V. V.; Maliszewszka-Kordibach, B.; Smreczak, B. (Acta Agraria Debreceniensis, 2012)
The efficiency of TENAX beads sorption method enabling to separate the bioavailable fraction of PAHs in the soil has been estimated. Due to the method the PAHs effects on soil biota have been explored. Laboratory investigations have ascertained possibility of application of TENAX beads sorption for soil quality assessment.